О конформных отображениях полигональных областей - Гутлянский, В.Я.; Зайдан, А.О. (Український математичний журнал, 1993)
The article deals with the development of P. P. Kufaiev's method for finding unknown parameters in the Schwarz – Christoffel integral for a conformai mapping of polygonal domains in the case of boundary normalizations.